TRESK contributes to pain threshold changes by mediating apoptosis via MAPK pathway in the spinal cord. (17th December 2016) - Zhou, Jun; Lin, Wenjing; Chen, Hongtao; Fan, Youling; Yang, Chengxiang
Highlights: Upregulation of TRESK alleviates hyperalgesia and neurons apoptosis induced by NP. Upregulation of TRESK inhibits activation of caspase 3 and upregulation of Bax. Upregulation of TRESK reduces inflammatory factors production in spinal cord. Downregulation of TRESK can induce to hyperalgesia in normal rats. TRESK contributes to pain threshold changes mediated by ERK and p38 MAPK. Abstract: The mechanism underlying neuropathic pain (NP) is complex and has not been fully elucidated. The TWIK-related spinal cord K + (TRESK) is the major background potassium current in dorsal root ganglia (DRG), we found that mitogen-activated protein kinase (MAPK) signal pathway were activated in spinal cord accompanied by TRESK down regulation in response to NP. Therefore, we investigated whether TRESK mediates inflammation and apoptosis by MAPK pathway in the spinal cord of NP rats. SNI rats exhibited reduced TRESK expression in DRG and spinal cord and higher sensitivity to mechanical stimuli but no effect on thermal stimuli. Intrathecal injections of TRESK overexpressing adenovirus alleviated mechanical allodynia, inhibited phosphorylation of extracellular signal-regulated kinase (ERK) and p38, and decreased inflammatory reactions and apoptosis in the spinal cords of SNI rats. Down regulation of TRESK in DRG and spinal cord was detected in normal rats after intrathecal TRESK shRNA lentivirus injection, which induced mechanical allodynia but had no effect on pain thresholds for heat stimulation. Phosphorylated ERK and p38 were increased in the spinal cord. Intrathecal injection of an ERK antagonist (PD98059) and p38 antagonist (SB203580) prevented ERK and p38 activation in the spinal cord and mechanical allodynia induced by TRESK shRNA lentivirus. In conclusion, our study clearly demonstrated an important role for TRESK in NP and that TRESK regulation contributes to pain sensitivity mediates inflammation and apoptosis by ERK and p38 MAPK signaling in the spinal cord.